2012
DOI: 10.1111/j.1540-8175.2012.01754.x
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Hypertrophy in Turner Syndrome: A Prospective Echocardiographic Study

Abstract: The increased left ventricular mass in TS was associated with aortic valve disease, age, hypertension, physical stature and metabolic status. During follow-up left ventricular mass was only slightly reduced along with blood pressure, whereas the diastolic dysfunction did not seem to improve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…The lower MGU and possibly increased cardiac metabolism of fatty acids may impair the metabolic profile and increase free radical formation with resulting apoptosis induced by lipo‐toxicity. Animal models have linked lipo‐toxicity with systolic and diastolic left ventricular dysfunction; a finding that is well aligned with a recent study in type 2 diabetics and echocardiographic findings in TS . However, the present study cohort did not show evidence of such findings despite a low MGU.…”
Section: Discussionsupporting
confidence: 92%
“…The lower MGU and possibly increased cardiac metabolism of fatty acids may impair the metabolic profile and increase free radical formation with resulting apoptosis induced by lipo‐toxicity. Animal models have linked lipo‐toxicity with systolic and diastolic left ventricular dysfunction; a finding that is well aligned with a recent study in type 2 diabetics and echocardiographic findings in TS . However, the present study cohort did not show evidence of such findings despite a low MGU.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, understanding of the impact of antihypertensive treatment in TS is very limited. However, recent data have suggested that left ventricular hypertrophy, an adverse cardiovascular prognostic factor, is ameliorated with treatment for hypertension in patients with TS . Counselling of patients with TS is highly dependent on that individual's risk of aortic dissection.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent data have suggested that left ventricular hypertrophy, an adverse cardiovascular prognostic factor, is ameliorated with treatment for hypertension in patients with TS. 34 Counselling of patients with TS is highly dependent on that individual's risk of aortic dissection. In the example of those seeking pregnancy, we feel that CMR is increasingly a valuable tool in both stratifying risk and monitoring for disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…1,25 Cardiomyopathy Left ventricular dysfunction and hypertrophy are common. 26 A plethora of metabolic and cardiovascular anomalies often seen in Turner syndrome can negatively impact the left ventricle, including insulin resistance, hypertension, aortic coarctation, and perturbed heart valve function. 26 Concentric left ventricular hypertrophy is common, associating with hypertension and bicuspid aortic valve, and myocardial metabolism has recently been found abnormal.…”
Section: Coronary and Systemic Arterial Diseasementioning
confidence: 99%
“…26 A plethora of metabolic and cardiovascular anomalies often seen in Turner syndrome can negatively impact the left ventricle, including insulin resistance, hypertension, aortic coarctation, and perturbed heart valve function. 26 Concentric left ventricular hypertrophy is common, associating with hypertension and bicuspid aortic valve, and myocardial metabolism has recently been found abnormal. 27 Even young females with no risk factors for myocardial disease have diastolic left ventricular dysfunction, and left atrial dilatation is common.…”
Section: Coronary and Systemic Arterial Diseasementioning
confidence: 99%